Effects of Palm-tocotrienol Rich Fraction (TRF) on OATP2 protein expression in Bilirubin Transport in adult rats - Ismawi, Hidayatul Radziah; Mohd Saad, Qodriyah; Ahmad Yusof, Asmadi; Othman, Faizah; Yusuf, Kamisah (2011)
OATP2 is a transport protein which is involved in bilirubin metabolism and excretion. Palm-tocotrienol rich fraction (TRF) has previously been shown to reduce total plasma bilirubin (TB). This study explored the effects of TRF pre-treatment on phenylhydrazine (PHZ) induced hyperbilirubinaemia in adult rats on bilirubin transport protein expression. Thirty-six adult male Wistar rats (200-250g) were divided into three groups; control (C), phenobarbital (PB) and TRF. TRF (100mg/kg/day, i.p.) and control (vitamin E free palm oil, i.p.) were given from the first day to the fourteenth day of study. For the PB group, normal saline (NS) was given for the first nine days and PB (80mg/kg/day, i.p.) was given for the next five days. On day 15, all the groups were further subdivided into two smaller groups. One group was given NS and the other group was given PHZ (C+NS, C+PHZ; PB+NS, PB+PHZ; TRF+NS, TRF+PHZ). After 24 hours, plasma TB was measured and liver tissue was taken for protein expression using Western Blot technique. TB was significantly higher in the C+PHZ group (0.19mg/dL +- 0.026) compared to C+NS group (0.06 mg/dL +- 0.008) TRF and PB did not reduce TB in PHZ-induced groups compared to the C+PHZ group. However, TB in the TRF+NS group was significantly lower compared to the C+NS and PB+NS groups. Treatment with TRF and phenobarbital increased the expressions of OATP2 in all groups compared to the control. In conclusion, TRF and PB increased the expressions of OATP2. However, TRF did not affect plasma TB in rats induced with PHZ.